Dispersion de esporas de Thecaphora frezii hacia nuevas areas productivas - Perez, Ignacio Agustin; Paredes, Juan Andrés; Mortigliengo, S.; Monguillot, Joaquín Humberto; Rago, Alejandro Mario (Centro de Ingenieros Agrónomos General Cabrera, 2022)
Resumen extendido